2015
DOI: 10.1002/hed.24003
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with 3‐(1′‐hexyloxyethyl) pyropheophorbide‐a for early‐stage cancer of the larynx: Phase Ib study

Abstract: BackgroundThe purpose of this study was for us to report results regarding the safety of 3‐(1′‐hexyloxyethyl) pyropheophorbide‐a (HPPH) mediated photodynamic therapy (PDT) in early laryngeal disease, and offer preliminary information on treatment responses.MethodsA single‐institution, phase Ib, open label, noncomparative study of HPPH‐PDT in patients with high‐risk dysplasia, carcinoma in situ, and T1 squamous cell carcinoma (SCC) of the larynx. The primary outcomes were safety and maximum tolerated dose (MTD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Based on this and several other studies, an HPPH dose of 4 mg/m 2 appears effective 1315 . A 2-day drug/light interval was allowed in this trial.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Based on this and several other studies, an HPPH dose of 4 mg/m 2 appears effective 1315 . A 2-day drug/light interval was allowed in this trial.…”
Section: Discussionsupporting
confidence: 55%
“…A 2-day drug/light interval was allowed in this trial. In more recently initiated studies the drug/light interval has been reduced to ~24 hours based on pharmacokinetic studies 25 yielding at least comparable effectiveness 14, 15 . Although a maximally tolerated light dose could not be firmly established, the one SAE/DLT that occurred at 150 J/cm 2 suggests that the light dose should not exceed 125 J/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Phase Ib study carried out at Roswell Park Cancer Institute examined response of laryngeal T1 squamous cell carcinoma of the larynx to HPPH treatment as a secondary outcome, and observed an 82% complete response rate. 12 …”
Section: Pdt For Early Stage Sccmentioning
confidence: 99%
“…Merrill A. Biel treated 115 patients with early laryngeal cancers, and concluded that PDT resulted in no glottic scarring as compared to conventional laser or surgical excision . Shafirstein et al reported that there was no damage to the mucosal wave of vocal folds after PDT in some patients with laryngeal carcinoma . Silbergleit et al reported that PDT yielded significant improvement in amplitude of vibration, mucosal wave, and nonvibrating portion of the vocal folds after treatment of laryngeal malignancies .…”
Section: Introductionmentioning
confidence: 99%